Implementación de un sistema eficiente para el calentamiento de agua por medio de paneles térmicos solares para el complejo turístico “señor del árbol - Pacheco Pacheco, Cristian Orlando (2018)
The Tourist Complex "Señor del árbol" located in the ecclesiastical Cuicuno needs to have weekly hot water and, for this purpose is used Liquefied Petroleum Gas Heaters, this means a high operating cost in addition to the latent risk of explosion as it is a hydrocarbon with high volatility, without forgetting the pollution that this element produces to the environment by his CO2 emissions. Consider these aspects is the need to implement a water heating system that replaces the main one, choosing in this case solar thermal panels that are: safe, economical operation, easy maintenance and long service life. To verify the feasibility of this, a solar radiation study was carried out in the sector, receiving average values of 800Wh /m2 with peaks over 1500 Wh /m2 ideal for this purpose, giving this the starting point for the development of the system with all its components as an accumulator system of hot water, circulation pumps, valves, accessories and automatic operation control. At the end of the implementation of the solar thermal panels, it was possible to move the previous system that was the main one to only an auxiliary system as they are able to maintain water at 38°C with the aforementioned radiation, in addition to the beneficial location of the complex at a latitude of -0.802688 that does not need to vary its inclination to improve performance.